ANALISIS PENGARUH PENGGUNAAN APLIKASI GEOGEBRA TERHADAP PEMECAHAN MASALAH MATEMATIS - Nabila Adawiyah; Heni Pujiastuti; Rofiroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of using GeoGebra on students’ mathematical problem-solving abilities. The research employed a Systematic Literature Review (SLR) method using the PRISMA approach through literature searches on Google Scholar with the assistance of Publish or Perish for articles published between 2022 and 2026. From 76 identified articles, 15 relevant articles were selected based on the inclusion criteria.The findings indicate that GeoGebra has a positive effect on students’ mathematical problem-solving skills. Its use helps improve conceptual understanding, mathematical visualization, learning engagement, and critical thinking skills. The effectiveness of GeoGebra becomes more optimal when combined with learning models such as Problem Based Learning, Realistic Mathematics Education, and Discovery Learning. Therefore, GeoGebra can be used as an innovative digital learning medium to support mathematics learning.